2017
DOI: 10.1021/acs.jpca.7b01857
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Product Distribution of the O3-Initiated Degradation of (E)-2-Heptenal, (E)-2-Octenal, and (E)-2-Nonenal

Abstract: The O-molecule initiated degradation of three 2-alkenals (E)-2-heptenal, (E)-2-octenal, and (E)-2-nonenal has been investigated in a 1080 L quartz-glass environmental chamber at 298 ± 2 K and atmospheric pressure of synthetic air using in situ FTIR spectroscopy to monitor the reactants and products. The experiments were performed in the absence of an OH scavenger. The molar yields of the primary products formed were glyoxal (49 ± 4) % and pentanal (34 ± 3) % from the reaction of (E)-2-heptenal with O, glyoxal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 67 publications
3
11
0
Order By: Relevance
“…Although ozonolysis of unsaturated VOCs is known to be a source of OH radicals and also a process that can lead to the formation of SOA, studies of atmospheric degradation of unsaturated aldehydes (>C4) by ozone are scarce, and data regarding the temperature‐dependent kinetics of these reactions are not available. To date, five kinetic studies, conducted in the relative mode, concerning the atmospheric degradation of unsaturated aldehydes by ozone, are available at room temperature . Atkinson et al and Grosjean et al studied the gas‐phase reaction of ozone with trans‐2‐hexenal.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although ozonolysis of unsaturated VOCs is known to be a source of OH radicals and also a process that can lead to the formation of SOA, studies of atmospheric degradation of unsaturated aldehydes (>C4) by ozone are scarce, and data regarding the temperature‐dependent kinetics of these reactions are not available. To date, five kinetic studies, conducted in the relative mode, concerning the atmospheric degradation of unsaturated aldehydes by ozone, are available at room temperature . Atkinson et al and Grosjean et al studied the gas‐phase reaction of ozone with trans‐2‐hexenal.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the gas‐phase reaction of ozone with C 5 ‐unsaturated aldehydes is limited to one investigation of trans‐2‐pentenal kinetics carried out by Sato et al at room temperature and under purified air pressure of 101 kPa, using the relative rate method. Gaona Colman et al reported the rate constants of 2‐methyl‐2‐pentenal with ozone at (298 ± 2) K and 760 Torr in an environmental chamber with in situ FTIR spectroscopy using a relative method. Ozonolysis of higher carbon containing unsaturated aldehydes (C7 to C9) was investigated by Gaona Colman et al at 298 K and (990 ± 10) mbar in an environmental chamber with in situ FTIR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…All the experiments were performed in a 1080 L quartz-glass reaction chamber at (298 AE 2) K and a total pressure of (760 AE 10) torr of synthetic air. A detailed description of the reactor can be found elsewhere 17,18 and only a brief description is given here. The photolysis system consists of 32 superactinic lamps (Philips TL05 40W: 320-480 nm, l max ¼ 360 nm) and 32 low-pressure mercury vapor lamps (Philips TUV 40W; l max ¼ 254 nm).…”
Section: Methodsmentioning
confidence: 99%